2013
DOI: 10.1111/een.12038
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal and dormancy strategies among insect species competing for a pulsed resource

Abstract: Dormancy and dispersal are thought to be major adaptive mechanisms that enable short‐lived organisms to cope with environmental stochasticity. The few empirical investigations that have explored the relationship between these two strategies in disturbed environments have focused mainly on communities of annual desert plants and suggest that dispersal plays a negligible role, as compared with dormancy, in reducing the risk of genotype extinction. We predict that the relative advantage of dormancy versus dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 46 publications
2
54
0
1
Order By: Relevance
“…Curculio species have moderate flight abilities and great diapause variability (with adults of the same cohort emerging over several years) (Pélisson et al, 2013), while Cydia exhibits good dispersal abilities but does not have any dormancy strategy (Schumacher et al, 1997). Curculio species have moderate flight abilities and great diapause variability (with adults of the same cohort emerging over several years) (Pélisson et al, 2013), while Cydia exhibits good dispersal abilities but does not have any dormancy strategy (Schumacher et al, 1997).…”
Section: Ruíz-carbayo Unpublished Results) Since the Onset Of Repromentioning
confidence: 99%
See 2 more Smart Citations
“…Curculio species have moderate flight abilities and great diapause variability (with adults of the same cohort emerging over several years) (Pélisson et al, 2013), while Cydia exhibits good dispersal abilities but does not have any dormancy strategy (Schumacher et al, 1997). Curculio species have moderate flight abilities and great diapause variability (with adults of the same cohort emerging over several years) (Pélisson et al, 2013), while Cydia exhibits good dispersal abilities but does not have any dormancy strategy (Schumacher et al, 1997).…”
Section: Ruíz-carbayo Unpublished Results) Since the Onset Of Repromentioning
confidence: 99%
“…). showing that C. glandium is able to disperse double the maximum distance estimated for C. elephas (1200 m vs. 600 m, respectively)(Pélisson et al, 2013). By contrast, C. glandium, which emerges in spring(Venner et al, 2011) and has a greater dispersal capacity, showed an evenly distributed infestation probability among forest types, just as Cydia did.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…, Pélisson et al. ). In fact for C. elephas , genetic differences and restricted gene flow among populations are observed beyond 300 m (H. Ruiz‐Carbayo, unpublished manuscript ).…”
Section: Methodsmentioning
confidence: 99%
“…Both C. glandium and C. elephas overwinter underground, but the two species present different phenologies: C. glandium emerges earlier, mostly in spring (Pélisson et al. ), while the emergence of C. elephas is restricted to autumn (Espelta et al. , Bonal et al.…”
Section: Methodsmentioning
confidence: 99%